PENGARUH DIKLAT DAN INOVASI TERHADAP KINERJA GURU SD SE KECAMATAN KOTA KISARAN BARAT KABUPATEN ASAHAN - Agustina, Kurnia (Smart Education, 2025)
Abstract: Teacher performance includes all activities carried out by teachers, namely planning, implementing and evaluating the learning process, and applying the evaluation results to improve the next learning process. Assessment of teacher performance is not only assessed from the level of student mastery of the material taught, but also assessed from how teachers make various preparations for learning to the stages of implementing learning. The objectives of this study are 1) To determine the extent of the influence of training on the performance of elementary school teachers in Kota Kisaran Barat District, Asahan Regency, 2) To determine the extent of the influence of innovation on the performance of elementary school teachers in Kota Kisaran Barat District, Asahan Regency, and 3) To determine the extent of the influence of training and innovation together on the performance of elementary school teachers in Kota Kisaran Barat District, Asahan Regency. The results of the study indicate that training has an effect on the performance of elementary school teachers in Kota Kisaran Barat District, Asahan Regency. There is a moderate effect of 56.90% where the better the training, the higher the teacher's performance. Innovation has an effect on the performance of elementary school teachers in Kota Kisaran Barat District, Asahan Regency. There is a moderate effect of 41.10% where the better the innovation, the higher the teacher's performance. Training and innovation simultaneously have an effect on the performance of elementary school teachers in Kota Kisaran Barat District, Asahan Regency. There is a significant effect of 94.90%. The determination coefficient R² of 89.80% can be explained by training and innovation simultaneously, and the remaining 10.20% is explained by other factors, such as work enthusiasm and competence variables. Keywords: Training, Innovation, Teacher Performance Abstrak: Kinerja guru meliputi semua aktivitas yang dilakukan oleh guru, yaitu merencanakan, melaksanakan dan mengevaluasi proses pembelajaran, serta menerapkan hasil evaluasi untuk memperbaiki proses pembelajaran selanjutnya. Penilaian terhadap kinerja guru tidak hanya dinilai dari tingkat penguasaan siswa terhadap materi yang diajarkan, tetapi juga dinilai dari sejak bagaimana guru melakukan berbagai persiapan untuk pembelajaran hingga tahapan pelaksanaan pembelajaran. Tujuan penelitian ini adalah 1) Untuk mengetahui besarnya pengaruh diklat terhadap kinerja guru SD Se Kecamatan Kota Kisaran Barat Kabupaten Asahan, 2) Untuk mengetahui besarnya pengaruh inovasi terhadap kinerja guru SD Se Kecamatan Kota Kisaran Barat Kabupaten Asahan, dan 3) Untuk mengetahui besarnya pengaruh diklat dan inovasi secara bersama-sama terhadap kinerja guru SD Se Kecamatan Kota Kisaran Barat Kabupaten Asahan. Hasil penelitian menunjukkan bahwa diklat berpengaruh terhadap kinerja guru SD Se Kecamatan Kota Kisaran Barat Kabupaten Asahan. Terdapat pengaruh yang sedang sebesar 56,90 % dimana semakin baik diklat maka kinerja guru juga akan semakin tinggi. Inovasi berpengaruh terhadap kinerja guru SD Se Kecamatan Kota Kisaran Barat Kabupaten Asahan. Terdapat pengaruh yang sedang sebesar 41,10 % dimana semakin baik inovasi maka kinerja guru juga akan semakin tinggi. Diklat dan inovasi secara simultan berpengaruh terhadap kinerja guru SD Se Kecamatan Kota Kisaran Barat Kabupaten Asahan. Terdapat pengaruh signifikan sebesar 94,90 %. Koefisien determinasi R² sebesar 89,80 % dapat dijelaskan oleh diklat dan inovasi secara serempak, dan sisanya 10,20 % lagi dijelaskan oleh faktor lain, yaitu seperti variabel semangat kerja dan kompetensi. Kata kunci: Diklat, Inovasi, Kinerja Guru